A computational DFT study of third order nonlinear optical properties of organic 4-chloroaniline (CA) crystal. (2020) - Andal, C.; Bharathi Devi, V.; Murugakoothan, P.
Abstract: The organic 4-Chloroaniline (CA) crystal was developed using slow evaporation solution method with ethanol solvent at room temperature. The single crystal XRD study is useful to confirm the crystal structure of the grown CA crystal. The linear optical properties of the grown CA crystal were calculated using UV–vis-NIR transmission spectrum study. The theoretical investigation of nonlinear optical property of the grown CA crystal was observed using the functional basic sets of B3LYP/6-31G (d, p) with the determination of its second order hyperpolarizability and also its optical behavior from HOMO-LUMO analyze. The theoretical values of second order hyperpolarizability and energy band gap are compared experimentally with Z-scan technique study and UV–vis-NIR transmission spectrum analyze.